Effectiveness of Physical Robot Versus Robot Simulator in Teaching Introductory Programming - Kurniawan, Oka; Tiong Seng Lee, Norman; Datta, Subhajit; Sockalingam, Nachamma; Pey Kin Leong (2018 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE), 2018)
This study reports the use of a physical robot and robot simulator in an introductory programming course in a university and measures students' programming background conceptual learning gain and learning experience. One group used physical robots in their lessons to complete programming assignments, while the other group used robot simulators. We are interested in finding out if there is any difference in the learning gain and experiences between those that use physical robots as compared to robot simulators. Our results suggest that there is no significant difference in terms of students' learning between the two approaches. However, the control group that uses the physical robot shows a more positive response in their attitudes towards computing. We discuss the implications of our findings in relation to engaging students and challenges in using physical robots from the learner perspectives and ways to alleviate this. Finally, by considering the insights from students' comments, we also suggest an alternative that may give both benefits of using both physical robots and robot simulators.